The prevalence of leucocytozoon toddi in bird blood samples in Aras - Iğdır and evaluation of its phylogenetic relationships - Akbaba, Özge. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2012., 2012)
Today biological diversity is faced with high risks of extinction due to the overuse of natural resources. Studies of bird species constitutes a central theme in ecological investigations and for conservation of biological diversity. The identification of parasitic infections encountered in birds provide contributions to ecological studies with regards to the persistence of species. This aim of this study is the detection of the prevalance of Leucocytozoon toddi infection in birds of Aras-Iğdır region, using genetic methods. 401 blood samples belonging to 58 bird species of 25 different families were investigated. L. toddi infection was detected in 41 samples and five distinct haplotypes were obtained from six sequences. Phylogenetic trees were constructed using these five haplotypes along with 265 sequences of 76 species taken from GenBank and MalAvi databases. Four out of five haplotypes of Aras-Iğdır positive samples were distinct from those in literature. Again four of the five Aras-Iğdır haplotypes clustered very closely together, potentially suggesting some genetic isolation in this migratory pathway. The phylogenetic comparisons made using all sequences also support the idea of the presence of two cryptic species of L. toddi.
Keywords: Leucocytozoon.; Upland game birds -- Parasites -- Iğdır.